How far can you go? - Lodge, David, ....- (Harmondsworth : Penguin books, 1985)
Polly, Dennis, Angela, Adrian and their peers were bound to lose their spiritual innocence as well as their virginities on the way from the 1950s to the '70s. On the one hand there was the traditional Catholic Church, on the other the siren call of the permissive society - the appearance of the pill, the disappearance of Hell and the advent of COC (Catholics for an Open Church). It was inevitable that things would change radically. But how far could it go? How far could they go? And where would it all end? Find out in this razor-sharp novel of satiric insight and comic despair.
Keywords: Fiction